Understanding the functional inflammatory factors involved in therapeutic response to immune checkpoint inhibitors for pan-cancer - Wu, Yanmeizhi; Yu, Shan; Qiao, Hong (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) fight tumor progression by activating immune conditions. The inflammatory factors are playing a functional role in programmed death-1 (PD-1) or other immune checkpoints. They are involved in regulating the expression of programmed death ligand-1 (PD-L1), the only predictor recognized by the guidelines in response to ICIs. In addition, abundant components of the tumor microenvironment (TME) all interact with various immune factors contributing to the response to ICIs, including infiltration of various immune cells, extracellular matrix, and fibroblasts. Notably, the occurrence of immune-related adverse events (irAEs) in patients receiving ICIs is increasingly observed in sundry organs. IrAEs are often regarded as an inflammatory factor-mediated positive feedback loop associated with better responses to ICIs. It deserves attention because inflammatory factors were observed to be different when targeting different immune checkpoints or in the presence of different irAEs. In the present review, we address the research progresses on the regulating inflammatory factors for an intentional controlling anti-cancer response with immune checkpoint inhibitors.